Antibiotic Susceptibility of the First Streptococcus Constellatus Isolated from Epidural Abscess in Dakar - Assane Dieng; Serigne ML Ndiaye; Khadidiatou Gueye; Frederic C Diaz; Samba Diao; Safi etou Ngom; Habsa Diagne; Moustapha Cisse; Maguette Diop; Pape I Ndiaye; Makhtar Camara; Cheikh SB Boye (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
Streptococcus constellatus can sometimes cause serious invasive infections, as infections of the liver and lung, brain abscesses, bacteraemia, endocarditis and intra-abdominal infections. The study aimed to identify S.constellatus and to assess their susceptibility to several antibiotics. Methods: In a 59-year-old patient hospitalized in intensive unit care for an epidural abscess, pus was collected and bacterial were grown, then bacterial identifi cation was performed by routine laboratory methods. Antimicrobial susceptibility testing was performed using standard disk diffusion method and MIC of several antibiotics was determined by using the BioMérieux Vitek 2. Results: S.constellatus was identifi ed in abscess and was resistant to penicillin, aminoglycosides, macrolides, lincomycin, and fl uoroquinolones. Only vancomycin, pristinamycin and rifampin were active. Conclusion: S.constellatus is considered commensal organism, but identifi cation and antibiotic susceptibility of this species are necessary for good management of the abscess.